PERAN SAINS DAN TEKNOLOGI DALAM PEMBANGUNAN PERMUKIMAN - Wirawibawa Mantra, Ida Bagus Gede (Jurnal Natah, 2012)
This paper is a literature review as an effort to perform a solution alternative of housing and settlement development problems. Indonesia country guideline (GBHN) as basis on the development, one of is housing and settlement sector, require to be held up by technology application and invention outcome of science i.e. there is a precedence to research and propose the solution as effort to solve immediately the housing and settlement development problem, scientific program and technology particularly using the local potential are able to enhance an efficiency, considering the labor absorption aspect and pay attention to the loss environment impact.
Keywords: science, technology, construction merit and building material.